Level of Awareness in Practicing Basic Safety Precautions in Relevance of Fire Prevention in Brgy San Agustin Novaliches Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Fire is one of the most serious disasters that threaten public safety and a major cause ofdamage to property, injury, and loss of life. It is important to know and be aware of the basicsafety precautions and relevance of fire prevention to reduce or eliminate the occurrence offire by training in fire safety, as well as in the proper maintenance and care of fire protectionand life systems and by counting potential ignition sources and fuels.It was discovered that the respondents are ages 20 - 25 and above, the majority of them areaware of practicing basic safety precautions in the relevance of fire prevention, and thechildren playing with fire is one of the main causes why fire incidents occurred in thecommunity based on the knowledge of respondent in Brgy San Agustin. The problemencountered by the respondents is human error, which means that untrained staff or anyonecan easily place combustible materials in the wrong place, which can cause fire incidents.
Keywords: Criminology